2010
DOI: 10.1002/clc.20806
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Annular Plane Systolic Excursion Evaluation Improves Selection of Cardiac Resynchronization Therapy Patients

Abstract: Background: The beneficial effects of cardiac resynchronization therapy (CRT) on left ventricular (LV) remodeling have been extensively described. Few data are available about the effects of CRT on right ventricular (RV) function and remodeling. Hypothesis: We hypothesized that CRT could also induce reverse remodeling in the right ventricle and that RV baseline functional status expressed as tricuspidal annular plane systolic excursion (TAPSE) could affect CRT response. Methods: Echocardiographic investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…Our results are in agreement with Capelli et al, 36 who demonstrated that CRT induces both RV and LV reverse remodeling, and is more effective in patients with higher TAPSE. In addition, Scuteri et al 32 concluded that low baseline TAPSE was associated with poor response and adverse prognosis, while Sade et al 37 showed that preserved RV function is an independent predictor of long-term event-free survival after CRT.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with Capelli et al, 36 who demonstrated that CRT induces both RV and LV reverse remodeling, and is more effective in patients with higher TAPSE. In addition, Scuteri et al 32 concluded that low baseline TAPSE was associated with poor response and adverse prognosis, while Sade et al 37 showed that preserved RV function is an independent predictor of long-term event-free survival after CRT.…”
Section: Discussionsupporting
confidence: 93%
“…These results match Damy et alCARE-HF (Cardiac Resynchronization-Heart Failure) trial which found that,Right ventricular dysfunction is a powerful determinant of prognosis among candidates for CRT, and also concluded that patients with lower TAPSE at baseline had a higher mortality, regardless of assigned treatment (P = 0.001).16 it also matches Cappelli et al who had shown relatively similar results their study. They found after a follow up of 6 months that TAPSE, at 17 mm is an optimal cut-off, yielded 64% sensitivity and 60% specificity in predicting CRT response (17) . Also Schmeisser et al used baseline RV-PA coupling (RV function related to pulmonary vascular afterload) and PA compliance and found it an independent predictors of left ventricular reverse remodeling after CRT (18) .…”
Section: Rv Reverse Remodelingmentioning
confidence: 99%
“…A few studies looked at the relation of previous RV dysfunction with CRT effect on LV and RV remodeling [9,51,56], showing that a low baseline TAPSE could predict a bad response to CRT.…”
Section: Imaging Predictive Factorsmentioning
confidence: 99%